Marriage from the Perspective of Child Protection Law and Human Rights - Erma Hari Alijana (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study analyzes the effectiveness of legal protection for children against early marriage in Indonesia, examining the issue through the lenses of human rights and family law. Despite the 2019 amendment to the Marriage Law raising the minimum age to 19, child marriage remains prevalent due to significant regulatory disharmony and judicial loopholes. Employing a normative-juridical method supported by empirical socio-legal data, this research investigates the conflict between the Child Protection Law and other statutes regarding the age of majority. The findings demonstrate that the